Analysis of the Effect of Cash Ratio on Corporate Bankruptcy Risk: Case Study of Manufacturing Companies - Tenripada, Andi Sakinah Yan; Wandira, Ika (Indonesian Operations Research Association (IORA), 2025)
This study aims to explore the relationship between cash ratio and bankruptcy risk using an empirical analysis approach, and relate it to the Altman Z-score model as an indicator of financial sustainability. By analyzing the financial statement data of companies listed on the stock exchange during the period 2019-2023, this study investigates the impact of liquidity measured by cash ratio on bankruptcy potential. Regression method is used to assess the relationship, while Altman Z-score serves as a tool to measure the financial health of the company. The results show that the cash ratio contributes little to reducing the risk of bankruptcy, yet firms with higher liquidity exhibit a better Z-score. These findings highlight the importance of liquidity management as a strategy to ensure the financial sustainability of firms in the face of bankruptcy challenges.